The Effectiveness of Chosen Partial Anthropometric Measurements in Individualizing Head-Related Transfer Functions on Median Plane - Hugeng Hugeng; Wahidin Wahab; Dadang Gunawan (Journal of ICT Research and Applications, 2011)
Individualized  head-related  impulse  responses  (HRIRs)  to  perfectly suit  a  particular  listener  remains  an  open  problem  in  the  area  of  HRIRs modeling.   We  have  modeled  the  whole  range  of  magnitude  of  head-related transfer  functions  (HRTFs)  in  frequency  domain  via  principal  components analysis  (PCA),  where  37  persons  were  subjected  to  sound  sources  on  median plane.   We  found  that  a  linear  combination  of  only  10  orthonormal  basis functions was sufficient to satisfactorily model individual magnitude HRTFs. It was our goal to form multiple linear regressions (MLR) between weights of basis functions acquired from PCA and chosen partial anthropometric  measurements in  order  to  individualize  a  particular  listener's  H RTFs  with  his  or  her  own anthropometries. We proposed a novel individualization method based on MLR of  weights  of  basis  functions  by  employing  only  8  out  of  27  anthropometric measurements.  The  experiments'  results  showed  the  proposed  method,  with mean  error  of  11.21%,  outperformed  our  previous  works  on  individualizing minimum  phase  HRIRs  (mean  error  22.50%)  and  magnitude  HRTFs  on horizontal  plane  (mean  error  12.17%)  as  well  as  similar  researches.  The proposed  individualization  method  showed  that  the  individualized  magnitude HRTFs could be well estimated as the original ones with a slight error.  Thus  the eight  chosen  anthropometric  measurements  showed  their  effectiveness  in individualizing magnitude HRTFs particularly on median plane.